Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Streptococcus agalactiae outbreaks in cultured golden pomfret, Trachinotus blochii (Lacépède), in Singapore - S M Chong; W K Wong; W Y Lee; Z B Tan; Y H Tay; X H Teo; L D Chee; C J Fernandez (Journal of Fish Diseases, 2017)

Molecular sex identification of painted storks (Mycteria leucocephala): using FTA cards, horizontal PAGE and quick silver staining - ELSIE Y. S. YEE; ZAINAL ZAHARI ZAINUDDIN; AHMAD ISMAIL; CHEE KONG YAP; SOON GUAN TAN (Journal of Genetics, 2016)

Identification of immune response‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) by next‐generation sequencing - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2016)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Non‐immune‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2015)

Putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g are involved in the early immune response of brown‐marbled grouper, Epinephelus fuscoguttatus, Forskal, to Vibrio alginolyticus - C‐F Low; M N Shamsudin; H‐Y Chee; M Aliyu‐Paiko; E S Idrus (Journal of Fish Diseases, 2014)
The gram‐negative bacterium, Vibrio alginolyticus , has frequently been identified as the pathogen responsible for the infectious disease called vibriosis. This disease is one of the major challenges facing brown‐marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. The objective of this study was to investigate the proteins involved in the immune response of brown‐marbled grouper fingerlings during their initial encounter with pathogenic organisms. To achieve this objective, a challenge experiment was performed, in which healthy brown‐marbled grouper fingerlings were divided into two groups. Fish in the treated group were subjected to intraperitoneal injection with an infectious dose of V. alginolyticus suspended in phosphate‐buffered saline ( PBS ), and those in the control group were injected with an equal volume of PBS . Blood samples were collected from a replicate number of fish from both groups at 4 h post‐challenge and analysed for immune response‐related serum proteins via two‐dimensional gel electrophoresis. The results showed that 14 protein spots were altered between the treated and control groups; these protein spots were further analysed to determine the identity of each protein via MALDI ‐ TOF / TOF . Among the altered proteins, three were clearly overexpressed in the treated group compared with the control; these were identified as putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g. Based on these results, these three highly expressed proteins participate in immune response‐related reactions during the initial exposure (4 h) of brown‐marbled grouper fingerling to V. alginolyticus infection.

The pathology of ‘scale drop syndrome’ in Asian seabass, Lates calcarifer Bloch, a first description - S Gibson‐Kueh; D Chee; J Chen; Y H Wang; S Tay; L N Leong; M L Ng; J B Jones; P K Nicholls; H W Ferguson (Journal of Fish Diseases, 2012)
This is the first pathological description of ‘scale drop syndrome’ (SDS) in Asian seabass, Lates calcarifer Bloch. Cumulative mortality was estimated at 40–50%. The vasculitis in all major organs including the skin and associated tissue necrosis was distinctive. The dermis overlying scale beds was often necrotic and associated with scale loss. Necrosis of splenic ellipsoids, renal glomeruli and choroid rete glands of eye were further hallmarks of a disease with systemic vascular involvement. The brain was not spared vascular damage, and the resulting multifocal encephalomalacia probably accounts for the spiral swimming behaviour in some affected fish. Other lesions included accentuated hepatic lobulation and gastric gland necrosis. Nuclear chromatin margination and karyolysis in hepatocytes, renal tubular epithelium and gastric and intestinal epithelium suggest specific targeting of cells. Basophilic cytoplasmic inclusions were present in spleen, kidney, liver, heart and choroid rete, but they were not prominent. Using transmission electron microscopy, two morphological forms of virions were observed: single‐ and double‐enveloped hexagonal virions. Based on size and morphology, these virions resemble iridovirus or herpesvirus. The cause of SDS is unknown, but the pathological changes, especially the vasculitis, suggest an infectious aetiology, possibly viral.

Quantitative T-cell interferon-gamma responses to Mycobacterium tuberculosis-specific antigens in active and latent tuberculosis - C. B. E. Chee; T. M. S. Barkham; K. W. KhinMar; S. H. Gan; Y. T. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Fusion of coregistered cross-modality images using a temporally alternating display method - J. S. Lee; B. Kim; Y. Chee; C. Kwark; M. C. Lee; K. S. Park (Medical & Biological Engineering & Computing, 2000)